Perencanaan Strategis Sistem Informasi pada Perusahaan XYZ di Palembang - Masidin, Nevin Julian; Meilinda, Meilinda; Dwitama, Agustio; Wijaya, Andri (MDP Student Conference, 2025)
Information system strategic planning is an important step in supporting business sustainability and growth, especially in today's digital era. XYZ Company in Palembang faces challenges in managing information systems, such as less than optimal data security, high manual usage (paper recording) in operations, and suboptimal use of data to support strategic decision making that can hinder efficiency and competitiveness. This study aims to develop an integrated information system strategy using the Ward and Peppard method, as well as SWOT and PESTLE analysis to evaluate the internal and external environment. The results of the analysis indicate the need to increase the use of digital technology for operational transformation and data-based decision making. So that this study can provide solutions for companies in utilizing information systems to improve efficiency, innovation, and competitiveness in the industry.